Performance of Non-Cooperative and Cooperative Subcarrier Allocation in OFDM Systems - Santhosh, G.; Ali, K.Shoukath; Sampath, Dr.P. (IJRDO - Journal of Electrical And Electronics Engineering, 2015)
In this paper, the performance of non-cooperative and cooperative relaying protocols for multi-user OFDM systems are analyzed and compared. The cooperative relaying protocol consists of Amplify and Forward relaying protocol and proposed Decode and Forward relaying protocol. The two subcarrier allocation algorithms are used in noncooperative and cooperative relaying protocols. 1. Throughput subcarrier allocation algorithm 2. Fairness subcarrier allocation algorithms are considered. Throughput subcarrier allocation algorithm to maximize the throughput of the systems and Fairness subcarrier allocation algorithm to prioritize the fairness in the multi-user OFDM systems. Proposed DF relaying protocol in terms of bit error rate and channel capacity shows the better performance compared to noncooperative and AF relaying protocol.